2001
DOI: 10.1002/bit.1118
|View full text |Cite
|
Sign up to set email alerts
|

Biohydrogen generation by mesophilic anaerobic fermentation of microcrystalline cellulose

Abstract: Sixteen batch experiments were performed to evaluate the stability, kinetics, and metabolic paths of heat-shocked digester (HSD) sludge that transforms microcrystalline cellulose into hydrogen. Highly reproducible kinetic and metabolic data confirmed that HSD sludge could stably convert microcrystalline cellulose to hydrogen and volatile fatty acids (VFA) and induce metabolic shift to produce alcohols. We concluded that clostridia predominated the hydrogen-producing bacteria in the HSD sludge. Throughout this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(43 citation statements)
references
References 38 publications
6
35
0
2
Order By: Relevance
“…The results shown in Fig. 1a and e were fully agreed with a number of investigators that they have used inorganic nitrogen sources such as ammonium hydrogen carbonate [10,[12][13][14] and ammonium chloride [15,16] in H 2 fermentation media, their results indicated that the lower yield they obtained it might be due to the nitrogen source and the microorganism(s) they were used, others have shown that when ammonium chloride replaced peptone as a nitrogen source, H 2 yields are halved [17] . These observations were attributed their lower hydrogen yield to the composition of the nitrogen source in fermentation medium they used.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The results shown in Fig. 1a and e were fully agreed with a number of investigators that they have used inorganic nitrogen sources such as ammonium hydrogen carbonate [10,[12][13][14] and ammonium chloride [15,16] in H 2 fermentation media, their results indicated that the lower yield they obtained it might be due to the nitrogen source and the microorganism(s) they were used, others have shown that when ammonium chloride replaced peptone as a nitrogen source, H 2 yields are halved [17] . These observations were attributed their lower hydrogen yield to the composition of the nitrogen source in fermentation medium they used.…”
Section: Resultssupporting
confidence: 86%
“…Among these sources, yeast extract was the best source of nitrogen for hydrogen production and these results agreed with the finding of Lay [10] he found that the cultures supplemented with yeast extract, tryptone and peptone produced higher H 2 yields with near complete sugar consumption among these sources, yeast extract was the best source of nitrogen for hydrogen production, they reasoned that yeast extract facilitated the highest production rate. , inoculum size 10% (v/v), I pH.…”
Section: Resultssupporting
confidence: 83%
“…8,9 Fermentation is generally preferred because it is technically simpler than photosynthesis and it generates H 2 from carbohydrate materials obtained as refuse or waste products. 10 Anaerobic bacteria use organic substances as the sole source of electrons and energy, converting them into H 2 . The reactions involved in H 2 production (eqs 1 and 2) are rapid and these processes do not require solar radiation, making them useful for treating large quantities of wastewater by using a large fermenter.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of microcrystalline cellulose as a substrate above 25 g L 71 inhibited hydrogen production, while at 8 g cellulose per g VSS a maximum hydrogen yield occurred (Lay 2001). Dissolved H 2 concentrations may also be related to stirring regime.…”
Section: Effect Of Substrate Concentration/agitation Speed On Hydrogementioning
confidence: 98%
“…Spore germination may require particular environmental conditions and take an appreciable period. In batch studies with heat-treated sludge inocula, a lag period of 2 days was observed for the municipal solid waste/sludge mixture (Kalia et al 1994), whereas it was 4 days for microcrystalline cellulose (Lay 2001). The interruption of feed (glucose and casein hydrolysate) during the start-up phase could trigger mixed anaerobic spore-formers to sporulate, and that sporulation could not be reversed by re-supply of glucose.…”
Section: Source Of Origin For Hydrogen-generating Microfloramentioning
confidence: 99%